(Meta-)framing strategic entrepreneurship. (November 2017) - Simsek, Zeki; Heavey, Ciaran; Fox, Brian Curtis
In this essay, we seek to focus scholarly discourse on the conceptual identity, boundaries, and precision of strategic entrepreneurship as an organizational construct. To give a "face" to a construct, lines must be drawn, marking off what it encompasses and what it does not. We, thus, first frame and assess prior conceptualizations from a construct clarity perspective. Our intent here is not to exhaustively catalogue all the varied conceptualizations available, but rather to map in lieu of burrow the content domain of strategic entrepreneurship as a theoretical construct, illuminate points of convergence and divergence, and reveal potential blind spots and ambiguities in extant definitions. Then, we advance a meta-framework for stimulating discourse around the key construct parameters. We say "meta-framework" because we do not seek to offer a "silver bullet" but rather advance a core set of questions to view strategic entrepreneurship with greater clarity and precision. We conclude with a set of suggestions for guiding and stimulating future research.